How Effectively do Authors and Publishers Manage the Process of Creating Successful Marketing Textbooks for Undergraduate Students? - Masikunas, George; Baverstock, Alison Mary (International Journal of the Book, 2013)
This original research explores the authorial role in the development of marketing textbooks for undergraduates. Concentrating on those working as co-authors of leading marketing textbooks, we found that they formed a highly industrious group who use their subject knowledge and writing experience to mediate the relationship between the publishing houses who commission them and the module leaders who select from their output. The key factors influencing the creation of successful marketing textbooks are identified within the context of the textbook's role to serve the needs of both pedagogue and learner. We explore how textbooks arise, from proposal stage to publication, the development of material (both textbook and supplementary) and in particular the working relationship between authors, co-authors and their publishers. While the authors consulted made individual responses, there is sufficient similarity in their experience to draw generalised conclusions.